Pancasila Based Teaching Materials in Differentiated Learning to Improve Elementary Students Literacy Competence - Ade Putri Puspitasari; Sani Aryanto; Yosi Gumala; Yohamintin Yohamintin (Multidisciplinary Journal of Social Sciences and Humanities, 2025)
The purpose of this research is to review how the use of Pancasila Student Profile-based teaching materials in the context of differentiated learning impacts the improvement of literacy competencies among elementary school students. The method in this research uses a literature review method with four stages, including: (1) collecting relevant data related to the use of teaching materials based on the Pancasila student profile and differentiated learning (2) the researcher presents the collected data (3) the researcher reduces and inventories the data (4) then, the researcher will conclude based on the results of verifying valid and reliable data. The findings from this study show that incorporating teaching materials centered around the Pancasila Student Profile in a differentiated learning environment has been successful in enhancing students' literacy skills. This approach not only supports a deep understanding of literacy concepts but also takes into account the diverse needs and potentials of each student. In conclusion, the use of Pancasila student profile-based teaching materials in differentiated learning can influence the literacy skills of elementary school students.